Determinants of environmental health factors associated with the risk of stunting among children under five in North Aceh District - Ibrahim Ibrahim; Safwan Safwan; Safridha Kemala Putri; T. Khairul Fadjri (AcTion: Aceh Nutrition Journal, 2025)
Stunting among children under five years of age remains a major public health concern and reflects long-term nutritional deficiencies, often linked to poor environmental health conditions. The North Aceh District reports a stunting prevalence higher than the provincial and national averages, indicating a critical research gap regarding the environmental determinants contributing to this burden in the region. This study aimed to analyze the association between environmental health factors and the risk of stunting among children under five years of age in North Aceh District. This quantitative cross-sectional study was conducted from April to August 2025 in the working areas of the Simpang Keramat and Kuta Makmur Public Health Centers. A total of 90 children under five were selected through purposive sampling. Data were collected using structured questionnaires and through direct observations. Instrument validity and reliability were assessed prior to data collection. Statistical analyses were performed using the chi-square test. The prevalence of stunting among children under five years of age was 54.4%. Significant associations were found between stunting and clean water availability (OR = 4.8; p < 0.001), latrine availability (OR = 5.1; p = 0.002), waste management practices (OR = 8.5; p < 0.001), household waste disposal (OR = 4.9; p < 0.001), and the presence of helminth eggs in feces (OR = 5.0; p = 0.001). Overall, inadequate household waste management was the strongest environmental determinant of child stunting. In conclusion, environmental sanitation conditions, particularly household waste management, play a substantial role in the risk of stunting in children under five years of age. Strengthening community-based sanitation interventions and improving household waste management practices may effectively reduce infection-related risks and lower the prevalence of stunting in North Aceh District.